Artificial Intelligence in Arabic Language Education: Applications, Perceptions, and Pedagogical Integration - K. M. A. Ahamed Zubair (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
The rapid evolution of educational technology has positioned artificial intelligence (AI) as a transformative force in linguistics, necessitating a transition from traditional route learning to technology-driven, interactive methodologies in Arabic language education. This unified review seeks to amalgamate findings from four distinct studies to assess the influence of AI integration on pedagogical methodologies, curriculum development, and specific linguistic competencies, including speaking and summarization skills, while also examining student perceptions of AI-driven audiolingual media. Utilizing a systematic review and synthesis of four research papers, the study evaluates qualitative and quantitative data from AI tool implementations and student surveys conducted at the Department of Arabic, The New College, Chennai, India. The results reveal that AI significantly enhances engagement by providing adaptive, personalized learning experiences, specifically improving speaking proficiency and summarization accuracy through audio-lingual tools. However, critical barriers remain, including inadequate digital infrastructure, a lack of specialized teacher training, and the absence of clear policy frameworks for ethical AI use. This study concludes that while AI has profound potential to modernize Arabic instruction by fostering interactive and inclusive environments, its sustainable integration requires strategic policy support, comprehensive pedagogical shifts, and equitable technological access. Strengthening these areas is vital for ensuring that AI serves as an effective catalyst for linguistic excellence and inclusive education within higher education contexts. By addressing these infrastructure and policy-related challenges, institutions can fully leverage AI's potential to reshape modern Arabic curriculum design and improve long-term student learning outcomes.